Effects of Theraband and lightweight dumbbell training on shoulder rotation torque and serve performance in college tennis players - Treiber, F. A.; Lott, J.; Duncan, J.; Slavens, G.; Davis, H. (The American Journal of Sports Medicine, 1998)
The effects of a four-week Theraband elastic tubing and lightweight dumbbell resistance program on concentric shoulder rotator strength and velocity of serve were observed. Varsity male and female tennis players (N = 22) were randomly assigned to control and experimental groups. The experimental group improved in slow and fast shoulder rotation torque as well as peak and average speed of serve. Men recorded higher measures on all factors and exhibited a greater imbalance in external to internal rotation torque ratios. Implication: Tubing and light weight training may have beneficial effects on serving performance and functional strength in college tennis players.